Elucidating the immunological landscape of acute myocardial infarction using an integrated single-cell enzyme and antibody quantification (iSEAQ) assay. (3rd May 2023) - Lim, S; Lu, R; Kwek, K Z; Lee, E; Cheung, K W; Chew, N W S; Woo, K L; Cheow, L F; Han, J Y
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Research Foundation Background: Characterizing enzyme secretion with surface antigen expression of circulating leukocytes provides deep immunological insights that may benefit diagnostics and therapeutics of acute myocardial infarction (AMI). Current methods are limited by laborious sample preparation, lengthy assay time and limited analytical throughput. Purpose: We aimed to develop a point-of-care platform for real-time, granular immune profiling of AMI during index hospitalization. Methods: We developed a system for a 40-min assay termed integrated single-cell enzyme and antigen quantification (iSEAQ), consisting of an integrated microfluidic device for a streamlined process to recover and isolate single leukocytes from whole blood, and a customized 5-channel high-speed droplet fluorescence cytometer for sensitive quantification of key protein activity resembling live leukocyte activity in-vivo (Figure 1). Using a panel of 2 secreted enzymes (granzyme B (GzB) and neutrophil elastase (NE)) and 3 surface antigens (cluster of differentiation (CD) 66b, CD3 and CD31), we tracked the longitudinal shift of immune functionality of 9 patients admitted for acute ST-segment elevation myocardial infarction (STEMI) patients (median age 52 years, 100% males) at 3 timepoints during the index hospitalization: 1) on admission prior to coronary revascularization, 2) within 24 hours of revascularization, and 3) pre-discharge. The 5-channel fluorescence data were imported using a python script and pre-processed, before piping into Numpy, Pandas, Scipy and UMAP library for data preparation and classification. Seaborn and Matplotlib were used for all data visualization and plots. Data was analyzed using student two-tailed t-tests, with a significance level of <5%. Results: Leveraging on its ability to dissect enzyme secretion by phenotype class, iSEAQ unraveled distinct contributions of CD31, NE and GzB from peripheral granulocytes, T lymphocytes and other cells (Figure 2). The majority immune response is expressed in CD66b+ granulocytes showing increased NE+ secretion and CD31 surface antigen expression denoted in Class 0 in Figure 2. Compared to samples from healthy donors and STEMI patients on admission, the NE+ and CD31+ expressions were significantly lower in pre-discharge samples of STEMI patients (p<0.05). iSEAQ also distinguished anterior from inferior STEMI, as evident from a significantly elevated NE+CD31-secretion for CD66b+ granulocytes in anterior STEMI (365±70 vs 83±35 fg, p < 0.001), showing preliminary promise in the ability of iSEAQ to risk stratify. Conclusion: iSEAQ provided a comprehensive granular immune atlas of the longitudinal immune responses to STEMI during hospital admission. With its open design for assay panel using commercial biosensors, iSEAQ is a potentially powerful tool for taking functionality snapshots of immune system in many diseases. Schematics of iSEAQ assay and design Deep leukocyte classification by iSEAQ